Dietary Milk Phospholipids Attenuate Chronic Stress‐Induced Changes in Behavior and Endocrine Responses across the Lifespan. Issue 3 (16th December 2021) - Schverer, Marina; Donoso, Francisco; Mitchell, Avery; Rea, Kieran; Fitzgerald, Patrick; Sen, Paromita; Roy, Bernard L.; Stanton, Catherine; Dinan, Timothy G.; Cryan, John F.; Schellekens, Harriët
Abstract : Scope: Increasing scientific evidence is validating the use of dietary strategies to support and improve brain health throughout the lifespan, with tailored nutritional interventions catering for specific life stages. Dietary phospholipid supplementations in early life and adulthood are shown to alleviate some of the behavioral consequences associated with chronic stress. This study aims to explore the protective effects of a tailored phospholipid‐enriched buttermilk on behavioral and endocrine responses induced by chronic psychosocial stress in adulthood, and to compare these effects according to the life stage at which the supplementation is started. Methods and Results: A novel developed phospholipid‐enriched dairy product is assessed for its effects on social, anxiety‐ and depressive‐like behaviors, as well as the stress response and cognitive performance following chronic psychosocial stress in C57BL/6J mice, with supplementation beginning in adulthood or early life. Milk phospholipid supplementation from birth protects adult mice against chronic stress‐induced changes in endocrine response to a subsequent acute stressor and reduces innate anxiety‐like behavior in non‐stressed animals. When starting in adulthood, the dietary intervention reverses the anxiety‐like phenotype caused by chronic stress exposure. Conclusion: Dairy‐derived phospholipids exert differential protective effects against chronic psychosocial stress depending on the targeted life stage and duration of the dietary supplementation. Abstract : Dairy‐derived phospholipids exert differential protective effects against chronic psychosocial stress in C57BL/6J mice depending on the life stage targeted and duration of supplementation. Milk phospholipid supplementation from birth protects adult mice against chronic stress‐induced increases in corticosterone plasma levels in response to acute stress. When starting in adulthood, the dietary intervention reverses the anxiety‐like phenotype caused by chronic psychosocial stress.